Упростите выражение

а) -3а²б⁴ × 4аб³

б) (-3а в 6 степени б²)³

ang18 ang18    2   25.11.2021 05:52    25

Ответы
lobanovartem2 lobanovartem2  25.11.2021 06:00

Пошаговое объяснение:

а)

- 3a {}^{2} b {}^{4} \times 4ab {}^{3} = \left(-3\right)^{1}a^{2}b^{4}\times 4^{1}a^{1}b^{3} =\left(-3\right)^{1}\times 4^{1}a^{2}a^{1}b^{4}b^{3} =\left(-3\right)^{1}\times 4^{1}a^{2+1}b^{4+3} =\left(-3\right)^{1}\times 4^{1}a^{3}b^{4+3} =\left(-3\right)^{1}\times 4^{1}a^{3}b^{7} =-12a^{3}b^{7}

б)

( - 3a {}^{6} b {}^{2} ) {}^{3} =\left(-3a^{6}b^{2}\right)^{3} =\left(-3\right)^{3}\left(a^{6}\right)^{3}\left(b^{2}\right)^{3} =-27\left(a^{6}\right)^{3}\left(b^{2}\right)^{3} =-27a^{6\times 3}b^{2\times 3} =-27a^{18}b^{2\times 3} =-27a^{18}b^{6}

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика